2015
DOI: 10.1007/s11431-015-5881-5
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic control of NACA 0021 airfoil model with spark discharge plasma synthetic jets

Abstract: Spark discharge plasma synthetic jets (SPJs) have been used for the active flow control study on an NACA 0021 straight-wing model in a wind tunnel. The model forces and moments were measured using a six-component sting balance at a 20 m/s wind speed. The aim was to explore the SPJ's effect on airfoil aerodynamic by examining SPJ generators' position along the chordwise and the jet flow direction about the chord. Near the wing leading edge, two SPJ generators raised the stall angle by 2° and increased the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…7. The control effect of conventional actuation is similar to the increase in the stall angle of the NACA0021 wing model by a PSJ in a previous study [10]. In addition, it is similar to the control effect of the NACA0021 wing model by a conventional synthetic jet with an injection angle of 90° adopted by Gu et al [28].…”
Section: Flow Field Comparison Under Different Actuation States At Di...supporting
confidence: 79%
See 1 more Smart Citation
“…7. The control effect of conventional actuation is similar to the increase in the stall angle of the NACA0021 wing model by a PSJ in a previous study [10]. In addition, it is similar to the control effect of the NACA0021 wing model by a conventional synthetic jet with an injection angle of 90° adopted by Gu et al [28].…”
Section: Flow Field Comparison Under Different Actuation States At Di...supporting
confidence: 79%
“…The results showed that the drag decreased by 13% at a wind speed of 20 m/s (Re c = 6.7 × 10 5 ). Subsequently, Liu et al [10] arranged two PSJ actuators at 0.15c from the leading edge to actively control the flow separation of a NACA0021 airfoil model. The drag coefficient decreased by 33.1%, and the lift-drag ratio increased by 104.2% at a wind speed of 20 m/s (Re c = 3.6 × 10 5 ).…”
mentioning
confidence: 99%
“…Separation control at moderate-Reynolds number ONERA; Xiamen University; UNINA [35,72,73] Jet noise control ONERA [12,74,75] Shock wave/boundary layer interaction control UT Austin; AFEU; NUDT [18,[76][77][78][79][80][81][82][83] In separation control cases, PSJs are typically issued upstream of the separation region, either in the wall-normal direction to create a quasi-streamwise counter-rotating vortex pair [84] or pitched and skewed with respect to the main flow to produce a single dominant streamwise vortex [12]. These vortices transport the high-momentum flow from the outer boundary layer to the near-wall region, resulting in a fuller boundary layer velocity profile and a reduction in boundary layer shape factor (1.3-1.2 in [84]).…”
Section: Institutions Representative Literaturesmentioning
confidence: 99%
“…At a freestream velocity of 40 m/s (chord-based Reynolds number: Re c = 1.2 × 10 6 ) and an angle of attack of 11.5 • , the separation region initially occupying half of the chord shrinks monotonically when the actuation frequency increases, and a fully attached flow is obtained at f d > 250 Hz. In [73], three PSJAs are employed to control the flow separation over an NACA 0021 wing model at U ∞ = 20 m/s and Re c = 3.4 × 10 5 . Different actuation locations (0.15c and 0.45c) and jet pitching angles (45 • and 60 • ) are examined.…”
Section: Institutions Representative Literaturesmentioning
confidence: 99%
“…26 Generated by the instantaneous energy deposition from a high voltage pulsed arc discharge, 27 the pressure within the actuator chamber can reach a value of hundreds of kilopascals. 28 Since PSJA has abundant advantages such as no need for moving parts and external air sources, 25 high jet velocity, [29][30][31] wide-bandwidth, 32 and extremely fast response, 33,34 its application prospects in the flow control field are becoming more and more promising. 35 Owning the merits of both simple structure and high instantaneous pressure rise, PSJA might be suitable to be an ice breaker.…”
Section: Introductionmentioning
confidence: 99%